On the identity of the art of sport - Lipiec, Józef (Physical education, sport and olympism from a pedagogical perspective, 2023)
From the tradition of the Olympic Games, as well as the modern Olympic movement, it is impossible to refer to the values and heritage of Greece as a catalogue of values shaping modern sports. Taking this aspect into account, the aim of this article is to answer the following questions: When and why happened the process of bringing sport closer to art? What determines the identity of a particular sport as a phenomenon of belonging to the same sphere of existence and the same field of human experience? Who is the artist in the circle of light? The answers to these questions will be taken through the prism of the concept of the unity of human virtues, as well as by referring to the tradition of Olympia from a historical, axiological, and essential perspective. Originally conceived, corporeality is the material of the art of sport as the material foundation of a specific and independent whole.